Anterior to Dorsal Root Entry Zone Myelotomy (ADREZotomy): A New Surgical Approach for the Treatment of Ventrolateral Deep Intramedullary Spinal Cord Cavernous Malformations. Issue 17 (1st September 2018) - Ren, Jian; He, Chuan; Hong, Tao; Li, Xiaoyu; Ma, Yongjie; Yu, Jiaxing; Ling, Feng; Zhang, Hongqi
Abstract : Study Design: A retrospective review of prospectively collected data. Objective: To confirm the feasibility of using anterior to dorsal root entry zone myelotomy (ADREZotomy), a new surgical approach, for the treatment of ventrolateral deep intramedullary spinal cord cavernous malformation (ISCCMs). Summary of Background Data: Surgical removal of ventrolateral deep ISCCMs is highly risky and remains problematic. Methods: The authors performed a retrospective study exploring the surgical removal of ventrolateral intrinsic ISCCMs using ADREZotomy in 10 patients. The Frankel grading system was used to evaluate the patients' neurological function at the preoperative, postoperative and follow-up stages. American Spinal Injury Association Scale scores at the preoperative and postoperative were also obtained. The patient characteristics and surgical outcomes were analyzed. The indication, operative steps, complications, and anatomical basis of the myelotomies were described and discussed. Results: In total, nine (90%) patients presented with mild symptoms before surgery. Gross total resections were performed in all 10 patients. Immediately after surgery, the neurological function of eight (80.0%) patients remained the same. One patient improved and one (10%) patient worsened. There were no other immediate or delayed complications related to the surgical procedure. No decrease of total American Spinal Injury Association sensory scores was observed. The follow-up neurological function evaluation showed that two (20%) patients improved from a Frankel grade of D to E and eight (80.0%) patients were stable. No recurrences or other additional neurological deterioration was observed. Conclusion: Surgical removal of ventrolateral deep ISCCMs can be feasible using proper surgical techniques. ADREZotomy is a minimally invasive technique for the removal of cervical and thoracic ventrolateral deep ISCCMs, without disrupting the important spinal cord tracts or the need to broadly expose bone. Level of Evidence: 4